Potential use of plant fibres and their composites for biomedical applications - Namvar, Farideh; Jawaid, Mohammad; Md. Tahir, Paridah; Mohamad, Rosfarizan; Azizi, Susan; Khodavandi, Alireza; Rahman, Heshu Sulaiman; Nayeri, Majid Dehghan (North Carolina State University, 2014)
Plant-based fibers such as flax, jute, sisal, hemp, and kenaf have been frequently used in the manufacturing of biocomposites. Natural fibres possess a high strength to weight ratio, non-corrosive nature, high fracture toughness, renewability, and sustainability, which give them unique advantages over other materials. The development of biocomposites by reinforcing natural fibres has attracted attention of scientists and researchers due to environmental benefits and improved mechanical performance. Manufacturing of biocomposites from renewable sources is a challenging task, involving metals, polymers, and ceramics. Biocomposites are already utilized in biomedical applications such as drug/gene delivery, tissue engineering, orthopedics, and cosmetic orthodontics. The first essential requirement of materials to be used as biomaterial is its acceptability by the human body. A biomaterial should obtain some important common properties in order to be applied in the human body either for use alone or in combination. Biocomposites have potential to replace or serve as a framework allowing the regeneration of traumatized or degenerated tissues or organs, thus improving the patients’ quality of life. This review paper addresses the utilization of plant fibres and its composites in biomedical applications and considers potential future research directed at environment-friendly biodegradable composites for biomedical applications.